Development of a direction-parallel strategy for shorting a tool path in the triangular pocket machining - Chaeron, Mochammad; Wahyuaji, Budi Saputro; Soepardi, Apriani (Jurnal Ilmiah Teknik Industri, 2019)
The machining strategy is one of the parameters which practically influences the time of the different manufacturing geometric forms. The machining time directly relates to the machining efficiency of the tool paths. In area milling machining, there are two main types of the tool path strategies: a direction-parallel milling and a contour-parallel milling. Then a direction-parallel milling is apparently simple compared with a contour-parallel strategy. In this paper, we propose a new model of the direction-parallel machining strategy for triangular pockets in order to reduce the tool path length. We have developed an analytical model by appending additional the tool path segments to the basic tool path for cutting un-machined area or scallops, which remained along the boundary. To validate our results, we have compared them to the existing model that found in the literature. For illustrating the computation of this model, the study includes two numerical examples. The results show that the proposed analytic direction-parallel model can reduce the total length of machining. Thus, it can take a shorter time for milling machining.